Ferritin Overexpression for Noninvasive Magnetic Resonance Imaging–Based Tracking of Stem Cells Transplanted into the Heart - Anna V. Naumova; Hans Reinecke; Vasily Yarnykh; Jennifer Deem; Chun Yuan; Charles E. Murry (Molecular Imaging, 2010)
An unmet need in cardiac cell therapy is a noninvasive imaging technique capable of tracking changes in graft size over time and monitoring cell dynamics such as replication and death, factors to which commonly used superparamagnetic nanoparticles are insensitive. Our goal was to explore if overexpression of ferritin, a nontoxic iron-binding protein, can be used for noninvasive magnetic resonance imaging (MRI) of cells transplanted into the infarcted heart. Mouse skeletal myoblasts (C2C12 cells) were engineered to overexpress ferritin. Ferritin overexpression did not interfere with cell viability, proliferation, or differentiation into multinucleated myotubes. Ferritin overexpression caused a 25% decrease in T 2 relaxation time in vitro compared to wild-type cells. Transgenic grafts were detected in vivo 3 weeks after transplantation into infarcted hearts of syngeneic mice as areas of hypointensity caused by iron accumulation in overexpressed ferritin complexes. Graft size evaluation by MRI correlated tighly with histologic measurements ( R 2 = .8). Our studies demonstrated the feasibility of ferritin overexpression in mouse skeletal myoblasts and the successful detection of transgenic cells by MRI in vitro and in vivo after transplantation into the infarcted mouse heart. These experiments lay the groundwork for using the MRI gene reporter ferritin to track stem cells transplanted to the heart.